Polychlorinated naphthalenes in human milk: Health risk assessment to nursing infants and source analysis. (March 2020) - Li, Cui; Zhang, Lei; Li, Jingguang; Min, Yihao; Yang, Lili; Zheng, Minghui; Wu, Yongning; Yang, Yuanping; Qin, Linjun; Liu, Guorui
Highlights: Concentrations of PCNs in human milks from China were firstly reported. Potential non-carcinogenic adverse health effects were suggested. Unintentional emission from thermal processes appears to be the main source. Abstract: Polychlorinated naphthalenes are teratogenic environmental contaminants. Mother milk is the most important food for nursing infants. The World Health Organization actively promotes breastfeeding for its immunological, psychological, and economic advantages. We firstly measured concentrations of polychlorinated naphthalenes in human milk from 19 provinces in China and estimated their potential health risks to nursing infants and their possible sources. Concentrations ranged from 211.07 to 2497.43 pg/g lipid. The high prevalence of highly toxic hexachlorinated naphthalenes (Hexa-CN66/67) in human milk samples indicated a higher health risk in the sampling areas. Cancer risk posed to nursing infants was not significant, but potential non-carcinogenic adverse health effects were suggested and should be emphasized in some sampling areas. Unintentional emission of polychlorinated naphthalenes from industries that employ thermal processes appears to be the main source for PCNs in human milk in most sampling areas. Correlation analysis also suggested PCNs as impurities in polychlorinated biphenyl mixtures as a previously unrecognized source of polychlorinated naphthalenes in human milk.